Rapid reduction of adenomyosis coexisting with leiomyoma volume during treatment with Relugolix - Keitaro Yamanaka; Keiichi Washio; Akiko Uchida; Yuki Sasagawa; Masashi Nishimoto; Yui Yamasaki; Satoshi Nagamata; Yoshito Terai (Taylor & Francis Group, 2023)
Objective This study elucidated the efficacy of Relugolix (REL) on the reduction of uterine volume and clinical symptoms for the treatment of adenomyosis.Methods We conducted a retrospective cohort study of patients who received REL (40 mg for about 20 weeks) and who underwent a hysterectomy for adenomyosis or fibroids. We divided patients into two groups: adenomyosis coexisting with fibroids (Group A) and fibroids only (Group B); the groups were determined by a postoperative pathological examination. The primary end points were the percent reduction in uterine volume, adenomyotic lesion, and the largest fibroid volume at week 16. The secondary end points were the rate of amenorrhea, pelvic pain, and anemia at week 12.Results A total of 56 patients participated in the current study: 20 in Group A and 36 in Group B. Regarding the largest fibroid volume, there was no significant difference between the two groups. Uterine volume after REL treatment was significantly decreased in Group A (43%), as compared to Group B (27%) (p = .00972), In Group A, adenomyotic lesion was decreased by 61%. Irrespective of the group, adenomyosis showed a significant reduction compared to uterine fibroids (p < .001). There was no statistically significant difference in the mitigation of symptoms (amenorrhea, pelvic pain, and anemia) between the two groups.Conclusions REL is more effective in reducing adenomyotic lesion than uterine fibroids and in relieving symptoms (amenorrhea, pelvic pain, and anemia). It can be expected that REL will also be used as a preoperative treatment for adenomyosis.